Humanness in times of uncertainty: On the link between perceived job insecurity, self‐objectification and well‐being. (30th October 2022) - Baldissarri, Cristina; Pagliaro, Stefano; Teresi, Manuel; Andrighetto, Luca
Abstract: The current work scenario is pervaded by widespread perceptions of job insecurity, which is one of the main stress factors for workers and their well‐being. This article aims to investigate the link between these perceptions and a most inner dimension, that is, people's tendency to self‐objectify (i.e., self‐viewing as objects rather than fully human beings). Furthermore, we aim to verify the role of this self‐objectifying process in explaining the well‐established relation between perceived job insecurity and well‐being. Across four studies and a single‐article meta‐analysis (total N  = 684), we show that perceived job insecurity is consistently linked with self‐objectification. Furthermore, this objectifying self‐perception is associated with decreased well‐being and plays a mediational role in the link between perceived job insecurity and this latter variable.